A General and Simple Diastereoselective Reduction by l-Selectride: Efficient Synthesis of Protected (4S,5S)-Dihydroxy Amides - Yin, Bo (Molecules, 2010)
A general approach to (4S,5S)-4-benzyloxy-5-hydroxy-N-(4-methoxybenzyl) amides 10 based on a diastereoselective reduction of (5S,6RS)-6-alkyl-5-benzyloxy-6-hydroxy-2-piperidinones 6 and their tautomeric ring-opened keto amides 7 is described. The reduction with l-Selectride at -20 °C to room temperature afforded the products 10 in excellent yields and moderate to high syn-diastereoselectivities.